2023
DOI: 10.1371/journal.pmed.1004091
|View full text |Cite
|
Sign up to set email alerts
|

Improving cascade outcomes for active TB: A global systematic review and meta-analysis of TB interventions

Abstract: Background To inform policy and implementation that can enhance prevention and improve tuberculosis (TB) care cascade outcomes, this review aimed to summarize the impact of various interventions on care cascade outcomes for active TB. Methods and findings In this systematic review and meta-analysis, we retrieved English articles with comparator arms (like randomized controlled trials (RCTs) and before and after intervention studies) that evaluated TB interventions published from January 1970 to September 30,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…A recent systematic review looking at interventions throughout the TB care cascade for active TB in mainly low-income and middle-income countries found that interventions that included counselling and education were significantly associated with treatment success. 56 A further systematic review assessing community-based TB interventions (such as electronic medication monitors, community health worker or family direct observation therapy) in low-income and middleincome countries found these approaches may improve treatment success while also offering convenience to patients. 57 Evidence on sex workers was limited to one single-arm study, and no studies were identified that focused on GRT populations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review looking at interventions throughout the TB care cascade for active TB in mainly low-income and middle-income countries found that interventions that included counselling and education were significantly associated with treatment success. 56 A further systematic review assessing community-based TB interventions (such as electronic medication monitors, community health worker or family direct observation therapy) in low-income and middleincome countries found these approaches may improve treatment success while also offering convenience to patients. 57 Evidence on sex workers was limited to one single-arm study, and no studies were identified that focused on GRT populations.…”
Section: Discussionmentioning
confidence: 99%
“…To improve TSR among previously treated persons with TB, barriers to suboptimal TSR like inadequate food, stigma, lack of social protection, frequent drug stock-outs and transportation challenges among others [25] should be addressed. The notable strategies might include strengthening health education on the importance treatment adherence and treatment completion [26] , and providing incentives like food support [27] , [28] and unconditional cash grants [29] , [30] . Strategies to assess treatment adherence like pill counts, three-day medication adherence recall, self-reported medication adherence, and pharmacy refills, which currently are not routinely used in TB care should be encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…TB-associated case mortality accounts for 25%-40% of global deaths and 18%-25% of admissions among PLHIV, despite treatment and detection advances. [13][14][15] In Ethiopia, 5.9% of HIV-positive patients newly enrolled in ART in 2016 had active TB (22). The country is among the top 10 TB burden countries, contributing to 87% of global TB cases (23).…”
Section: Introductionmentioning
confidence: 99%
“…The twin epidemic of TB and HIV caused 0.3 million deaths worldwide in 2017, with a lifetime risk increase from 15% to 22% (1). TB‐associated case mortality accounts for 25%–40% of global deaths and 18%–25% of admissions among PLHIV, despite treatment and detection advances 13–15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation